Search for excited and exotic muons in the μy decay channel in pp - collisions at s=1.96 TeV - Abulencia, A; Acosta, D; Adelman, J; Affolder, T; Akimoto, T; Albrow, MG; Ambrose, D; Amerio, S; Amidei, D; Anastassov, A; Anikeev, K; Annovi, A; et al. (2006)
We search for excited and exotic muon states * using an integrated luminosity of 371pb-1 of pp collision data at s=1.96TeV. We search for associated production of * followed by the decay *. We compare the data to model predictions as a function of the mass of the excited muon M *, the compositeness energy scale , and the gauge coupling factor f. No signal above the standard model expectation is observed. We exclude 107